Comparison of β-1,3-glucanase production by Botryosphaeria rhodina MAMB-05 and Trichoderma harzianum Rifai and its optimization using a statistical mixture-design - Giese, Ellen C. [UNESP]; Dekker, Robert F.H.; Scarminio, Ieda S.; Barbosa, Aneli M.; da Silva, Roberto [UNESP] (Elsevier, 2011)
Botryosphaeria rhodina MAMB-05 produced β-1,3-glucanases and botryosphaeran when grown on glucose, while Trichoderma harzianum Rifai only produced the enzyme. A comparison of long-term cultivation (300h) by B. rhodina demonstrated a correlation between the formation of botryosphaeran (48h) and its consumption (after 108h), and de-repression of β-1,3-glucanase synthesis when glucose was depleted from the nutrient medium, whereas for T. harzianum enzyme production commenced during exponential growth. Growth profiles and levels of β-1,3-glucanases produced by both fungi on botryosphaeran also differed, as well as the production of β-1,3-glucanases and β-1,6-glucanases on glucose, lactose, laminarin, botryosphaeran, lasiodiplodan, curdlan, Brewer's yeast powder and lyophilized fungal mycelium, which were dependent upon the carbon source used. A statistical mixture-design used to optimize β-1,3-glucanase production by both fungi evaluated botryosphaeran, glucose and lactose concentrations as variables. For B. rhodina, glucose and lactose promoted enzyme production at the same levels (2.30UmL -1), whereas botryosphaeran added to these substrates exerted a synergic effect favorable for β-glucanase production by T. harzianum (4.25UmL -1). © 2010 Elsevier B.V.
Keywords: β-1,3-Glucanases; Botryosphaeran; Statistical mixture-design optimization; Botryosphaeria rhodina MAMB-05; Carbon source; Curdlan; De-repression; Enzyme production; Exponential growth; Glucanase; Laminarins; Nutrient medium; Synergic effects; Trichoderma harzianum Rifai; Design; Enzymes; Fungi; Glucose; Mixtures; Optimization; 1,3 beta glucanase; curdlan; glucose; lactose; laminaran; botryosphaeria rhodina; comparative study; correlation analysis; enzyme substrate; enzyme synthesis; fungus; Hypocrea lixii; mycelium; nonhuman; priority journal; statistical analysis; Botryosphaeria rhodina